The Unified Clinical Protocol “Acute Stress Reaction. Post-Traumatic Stress Disorder. Adjustment Disorders” as a Basis for the Practical Training of Psychiatry Interns in Providing Medical Care to Patients with Anxiety-Phobic Disorders - Ohorenko Вікторія; Shusterman Тамара; Nikolenko Алла; Hrytsai Альона (Psychosomatic Medicine and General Practice, 2026)
Background. The ongoing war in Ukraine has led to an increased prevalence of anxiety-phobic disorders, highlighting the need for high-quality training of psychiatrists in providing primary and specialized mental health care. Mastering the Unified Clinical Protocol “Acute Stress Reaction. Post-Traumatic Stress Disorder. Adjustment Disorders” through practice-oriented educational approaches is an essential component of such training. Methods. The study involved 19 psychiatry interns undergoing the educational stage of internship training at the Department of Psychiatry, Narcology and Medical Psychology of Dnipro State Medical University. A case-based learning approach was used to master the provisions of the Unified Clinical Protocol through the analysis of clinical scenarios and practical training in psychological first aid and psychotherapeutic interventions. Results. A structured model for mastering the Protocol using case-based learning was developed and implemented. Clinical cases involving panic attacks, hysteria-like reactions, and fear were used to develop psychological first aid skills. Trauma-focused cognitive behavioral therapy techniques, including the “Downward Arrow” and “Reductio ad Absurdum” methods, were applied to train psychotherapeutic competencies. The use of clinical cases promoted the development of clinical reasoning, decision-making skills, and practical application of treatment algorithms for patients with anxiety-phobic disorders. Discussion. Case-based learning enabled the simulation of various clinical situations and facilitated the integration of theoretical knowledge with practical competencies. The approach proved useful for mastering psychological first aid algorithms and psychotherapeutic techniques aimed at modifying dysfunctional beliefs and catastrophic thinking patterns underlying anxiety-phobic disorders. Conclusions. Case-based learning is an effective tool for mastering the Unified Clinical Protocol “Acute Stress Reaction. Post-Traumatic Stress Disorder. Adjustment Disorders” during psychiatry internship training. The proposed approach facilitates the acquisition of psychological first aid and specialized psychotherapeutic skills and may be recommended for broader implementation in postgraduate medical education. Keywords: anxiety-phobic disorders, psychiatry interns, case-based learning, psychological first aid, trauma-focused cognitive behavioral therapy, clinical protocol, postgraduate medical education.